Indoor UAV crowd investigation – part 1 - Wong, Jin Yi (Nanyang Technological University, 2021)
This project report details the development of a modified path planning algorithm developed via the modification and combination of the RRT* algorithm with a path optimisation algorithm based on the tightening of strings. The path optimisation algorithm was tested for its performance and found suitable to be used in the path planning algorithm. Further developments based on the results of this project were proposed and attempted but were met with technical difficulties.